ANALYSIS OF BORON, CADMIUM AND IRON IN THORIUM NITRATE BY ICP-AES METHOD AFTER MATRIX SEPARATION USING TRIBUTYL PHOSPHATE - Sahat Simbolon (Jurnal Teknologi Bahan Nuklir, 2012)
ABSTRACT ANALYSIS OF BORON, CADMIUM AND IRON IN THORIUM NITRATE SOLUTION BY ICP–AES METHOD AFTER MATRIX SEPARATION USE OF TRIBUTYL PHOSPHATE. Analysis impurities elements in aqueous phase after thorium extraction with TBP-kerosen by ICP-AES method were carried out. A series of synthesized standards mixture of boron, cadmium and iron were prepared and each standards were measured 7 (seven) replicates for each elements for setting up calibration curve of boron, cadmium and iron. Aqueous samples solutions containing thorium less than 100 ppm and impurities elements boron, cadmium and iron solutions were analyzed by ICP-AES. All impurities elements were analyzed in optimum condition. It was found that minimum detection limit for boron 0.5 ppm, for cadmium 0.4 ppm and for iron 0.2 ppm. Boron, in three of the five samples, could be detected their presence but it could not be quantified statistically, and in two other samples their presence could be detected and quantified statistically. Boron concentrations were also calculated by first and second order of calibration curve and the difference between them was also depicted. It was found that cadmium had lower concentration than its minimum detection limit in all samples. On the other hand, It was found that iron had higher concentration than its minimum detection limit in all samples. Boron concentrations were also calculated by deterministic and probabilistic model. It was found that range of lower and upper concentration as a result of the prediction formula calculation is the widest and the shortest interval is caused by confidence formula, meanwhile samples measured seven times is closed to confidence formula. Keywords: Analysis, boron, cadmium, iron, thorium nitrate, tributyl phosphate, ICP-AES. ABSTRAK ANALISIS BORON, KADMIUM DAN BESI DI DALAM LARUTAN TORIUM NITRAT DENGAN METODA ICP-AES SETELAH PEMISAHAN MATRIKS MENGGUNAKAN TRI BUTIL FOSFAT. Telah dilakukan analisis unsur-unsur takmurnian di dalam fasa air setelah ekstraksi torium dengan campuran TBP-kerosin menggunakan metoda ICP-AES. Satu seri larutan standar sintesis yang terdiri dari campuran boron, kadmium dan besi dan setiap standar diukur 7 (tujuh) kali untuk setiap unsur dipersiapkan untuk membuat kurva kalibrasi setiap unsur. Larutan cuplikan yang mengandung torium lebih kecil dari 100 ppm dan unsur–unsur takmurnian dianalisis dengan ICP-AES. Semua unsur takmurnian dianalisis dalam kondisi optimum. Didapatkan batas deteksi minimum untuk boron 0,5 ppm, kadmium 0,4 ppm dan besi 0,2 ppm. Keberadaan boron, di dalam tiga cuplikan dari lima cuplikan tidak dapat ditentukan secara kuantitatif dan dua cuplikan lainnya terdeteksi dan dapat ditentukan secara kuantitatif. Konsentrasi boron juga ditentukan dengan menggunakan kurva kalibrasi orde pertama dan kedua dan perbedaannya juga digambarkan. Didapatkan bahwa kandungan unsur kadmium lebih rendah daripada batas deteksi untuk kelima cuplikan. Sebaliknya, didapatkan bahwa kandungan unsur besi pada semua cuplikan lebih besar daripada batas deteksinya. Konsentrasi boron juga dihitung dengan menggunakan model deterministik dan probalilistik. Diperoleh hasil bahwa kisaran konsentrasi antara yang paling rendah dan paling tinggi sebagai hasil dari model prediksi merupakan interval terluas dan lebih sempit jika digunakan model konfidens (kepercayaan), sedangkan cuplikan yang diukur tujuh kali diselesaikan dengan model kepercayaan. Kata kunci: Analisis, boron, kadmium, besi, thorium nitrat, tributil fosfat, ICP-AES